2009
DOI: 10.1007/bf03327448
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of functional decline during hospitalization in the oldest old

Abstract: ABSTRACT. Background and aims:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…We therefore classified units according to their purpose, followed by a test of the internal homogeneity of each class and finally including the unit purpose variable in our predictor analyses. Previous studies have found different variables that predict LOS, such as number of medical comorbidities, MMSE score, functional status, Tinetti Scale score, and degree of social support [4,[25][26][27][28]. Our results support previous findings: although the unit purpose variable explained most of the LOS total variability, reason for admission, and BRASS score variables were still significant predictors.…”
Section: Discussionsupporting
confidence: 92%
“…We therefore classified units according to their purpose, followed by a test of the internal homogeneity of each class and finally including the unit purpose variable in our predictor analyses. Previous studies have found different variables that predict LOS, such as number of medical comorbidities, MMSE score, functional status, Tinetti Scale score, and degree of social support [4,[25][26][27][28]. Our results support previous findings: although the unit purpose variable explained most of the LOS total variability, reason for admission, and BRASS score variables were still significant predictors.…”
Section: Discussionsupporting
confidence: 92%
“…Measuring functional decline is of interest, similarly to the concept of frailty, for its ability to predict future mortality, morbidity, hospitalisation and institutionalisation [40][41][42]. Increased risk is associated with cognitive impairment, hospitalisation, poly-pharmacy, older age, history of fractures, malnutrition, low physical activity, lower strength, and depression [41][42][43][44][45][46][47][48][49].Musculoskeletal conditions have long been recognised as a major cause of functional impairment and disability.…”
Section: Functional Decline and Its Role In Frailtymentioning
confidence: 99%
“…Increased risk is associated with cognitive impairment, hospitalisation, poly-pharmacy, older age, history of fractures, malnutrition, low physical activity, lower strength, and depression [41][42][43][44][45][46][47][48][49].Musculoskeletal conditions have long been recognised as a major cause of functional impairment and disability. The total number of disability adjusted life years associated with musculoskeletal conditions worldwide has been estimated as over 30,000,000, and they remain one of the ten leading causes of disability worldwide [50].…”
Section: Functional Decline and Its Role In Frailtymentioning
confidence: 99%
“…In particular, survival rates are low, with one study identifying that 33.9% of patients admitted from a residential care facility died during the hospital admission 25. In addition, morbidity associated with hospitalisation is high for this population, with increased incidence of delirium, infections and overall functional decline during a hospital admission 26 27. Furthermore, mortality is high in residential care settings after an admission to hospital 28.…”
Section: Discussionmentioning
confidence: 99%